2020
DOI: 10.1101/2020.03.30.015545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sickness behaviour reduces network centrality in wild vampire bats

Abstract: 11Sickness behaviours, like lethargy, can slow the spread of pathogens across a social network. 12We conducted a field experiment to investigate how sickness behaviour reduces individual 13 connectedness in a high-resolution dynamic social network. We captured adult female vampire 14 bats (Desmodus rotundus) from a wild roost. To create 'sick' bats, we injected a random half of 15 the bats (n=16) with the immune-challenging substance, lipopolysaccharide, and injected 16 control bats with saline (n=15). Over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Still, sickness behavior and its role in preventing pathogen transmission is poorly studied in bats. In the only previously studied species, LPS-injected vampire bats (Desmodus rotundus) decreased overall activity levels, reduced grooming towards others, received less grooming from group mates 30,32 , and had lower network centrality 21 yet there was no reduction in the number of food donors or the amount of food received following a night of food deprivation 32 . Such behavioral changes support the hypothesis that sickness behaviors alter interactions by which diseases are transmitted 5,30 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Still, sickness behavior and its role in preventing pathogen transmission is poorly studied in bats. In the only previously studied species, LPS-injected vampire bats (Desmodus rotundus) decreased overall activity levels, reduced grooming towards others, received less grooming from group mates 30,32 , and had lower network centrality 21 yet there was no reduction in the number of food donors or the amount of food received following a night of food deprivation 32 . Such behavioral changes support the hypothesis that sickness behaviors alter interactions by which diseases are transmitted 5,30 .…”
mentioning
confidence: 97%
“…Such variation demands refinement of the classical sickness behavior hypothesis to account for interspecific and contextual variation. Importantly, sickness behavior has been rarely investigated in free-ranging animals 18,19 with only two studies on free-ranging wild mammals demonstrating behavioral changes during sickness 20,21 .…”
mentioning
confidence: 99%
“…Here, we mimicked a bacterial infection in vampire bats using lipopolysaccharide (LPS) to trigger transient physiological symptoms and sickness behaviours [2,3,25], and then we tested for the effect of LPS on contact calling behaviour. LPS-injected vampire bats are groomed by fewer bats and have lower social connectedness in the wild, an effect that could be driven in part by a reduction in contact calling [3,25]. We show that LPS-induced sickness behaviour decreases the number of contact calls produced by isolated vampire bats.…”
Section: Introductionmentioning
confidence: 99%
“…Besides courtship vocalizations, a broader range of vocal interactions could be influenced by 60 sickness, but these other call types have received less attention. In many group-living animals that live in 61 conditions of low visibility, or that must maintain cohesion while on the move, individuals produce 62 contact calls to maintain contact with groupmates or particular affiliated individuals (Arnold and 63 bats are groomed by fewer bats and have lower social connectedness in the wild, an effect that could be 82 driven in part by a reduction in contact calling (Ripperger et al, 2020;Stockmaier et al, 2020). We show 83 that LPS-induced sickness behavior decreases the number of contact calls produced by isolated vampire 84 bats.…”
mentioning
confidence: 99%
“…In LPS trials, we induced sickness behavior in subjects 99 by injecting them subcutaneously with lipopolysaccharide (LPS, L2630 Sigma-Aldrich, USA, dose: 5 100 mg/kg body mass of bat) in phosphate-buffered saline (PBS) before the recording period. We chose this 101 dose based initially on observed effects in another bat species (Stockmaier et al, 2015), and on later 102 studies in vampire bats, which showed that this dose increases white blood cell count and neutrophil to 103 lymphocyte ratio (Stockmaier et al, 2018) and decreases in physical activity, social encounters, and social 104 grooming (Ripperger et al, 2020;Stockmaier et al, 2020Stockmaier et al, , 2018. In control trials, the same bats were 105 injected with an equivalent volume of only PBS as a control treatment.…”
mentioning
confidence: 99%